Studies on subfamily Aphodiinae (Coleoptera: Scarabaeoidea: Scarabaeidae) with description of three new species from the genera Agrilinus Mulsant & Rey, 1869, Gilletianus Balthasar, 1933 and Trichiorhyssemus Clouët, 1901 - Minkina, Łukasz (Zootaxa, 2022)
Three new species of Aphodiinae are described: Agrilinus matusiaki Minkina, new species from China, Gilletianus miurai Minkina, new species from Indonesia and Trichiorhyssemus immaturus Minkina, new species from China. Generic assignment of Agrilinus inexspectatus (Balthasar, 1935) is briefly discussed.                Agrilinus matusiaki Minkina, new species is described, illustrated and compared with the most similar species not only from genus Agrilinus Mulsant & Rey, 1869, but also with the somewhat similar Carinaulus Tesař, 1945. Gilletianus miurai Minkina, new species is described, illustrated and compared with the most similar species G. sundainsulanus Ochi, Kon & Kawahara, 2014. Some new or revised distribution records of the genus Gilletianus Balthasar, 1933 are given. Trichiorhyssemus immaturus Minkina, new species is described and illustrated. The newly described species has characters intermediate between the genera Trichiorhyssemus Clouët, 1901 and Neotrichiorhyssemus Rakovič & Král, 1997 and because of this the limits of these genera are discussed.